(untitled) (Research, Society and Development, 2024)
Abstract: It is up to the nurse directly responsible for the care to pay greater attention to preventing PI in elderly people in the hospital, as they are surrounded by predisposing factors, including integumentary aging. Objective: To present efficient methods of preventing pressure injuries in elderly patients in the hospital in nursing care. Methodology: This is an integrative review study. Articles, magazines, scientific research were used, from the following databases: Scientific Electronic Library Online (SCIELO), Latin American Literature in Health Sciences (LILACS), Virtual Health Library (VHL), using the keywords: Health Care Nursing, Prevention, Pressure Injury, Elderly, Hospital. Results: The types of studies selected are descriptive, cross-sectional and quantitative, with the qualitative methodological approach present in more than 60% of the articles and predominant in nursing journals, highlighting nursing assistance in the prevention of pressure injuries, the incidences of injuries and predisposing factors, with advanced age as a specific risk, a factor that makes patients vulnerable, especially in ICUs. Final Considerations: In this scenario, ensure the provision of nursing care with quality standards based on qualification, humanization of care, management of risk reduction and control for users and adherence to proven effective PI preventive care protocols in all services health system in the country, are essential behaviors that reduce the risk of injury and the risk of infection in elderly patients in the hospital, ensuring a reduction in injuries and length of stay.